Theory and treatment in depression: Towards an integration? - Luyten, Patrick (2003)
Recent research has changed our view on depression in important ways. The National Institute of Mental Health (NIMH) Strategic Plan for Mood Disorders Research (NIMH, 2003) is currently the most ambitious attempt to give a new impetus to research on mood disorders, and to develop more encompassing theories that will ultimately lead to more effective treatment strategies. However, in our view, this strategic plan fails to address several important issues and recent developments in research on depression. In this article, several important points of divergence are outlined with special reference to a conference on the integration of theories and treatment strategies on depression held in Kortenberg (Belgium) on March 14, 2003.